1978
DOI: 10.1136/bmj.1.6128.1664
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing postoperative morbidity and mortality in patients treated with bleomycin.

Abstract: associate chairman, department of anaesthesiology GRAZIANO C CARLON, MD, co-director, critical-care unit ESTEBAN CVITKOVIC, MD, associate physician, solid tumour service, department of medicine OLGA SCHWEIZER, MD, attending anaesthesiologist WILLIAM S HOWLAND, MD, chairman, department of anaesthesiology going removal of retroperitoneal lymph nodes or pulmonary metastases several preventive factors were established. These were the use of low concentrations of inspired oxygen during operation and in the immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

1978
1978
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(54 citation statements)
references
References 9 publications
1
51
0
2
Order By: Relevance
“…Cyclophosphamide, vincristine, doxorubicin, and methotrexate with bleomycin have also been reported to increase the risk of fi brosis. 7 Goldiner et al 78 reported that the use of oxygen therapy (mean concentration, 39%) during and after pulmonary resection in fi ve patients with testicular cancer who were treated with bleomycin (400 Ϯ 180 mg) 6 to 12 months prior, resulted in 100% mortality because of respiratory distress. Postmortem examination showed severe alveolar wall damage consistent with bleomycin-induced pulmonary injury.…”
Section: Pulmonary Function and Loss Of Optimal Exercise Capacitymentioning
confidence: 99%
“…Cyclophosphamide, vincristine, doxorubicin, and methotrexate with bleomycin have also been reported to increase the risk of fi brosis. 7 Goldiner et al 78 reported that the use of oxygen therapy (mean concentration, 39%) during and after pulmonary resection in fi ve patients with testicular cancer who were treated with bleomycin (400 Ϯ 180 mg) 6 to 12 months prior, resulted in 100% mortality because of respiratory distress. Postmortem examination showed severe alveolar wall damage consistent with bleomycin-induced pulmonary injury.…”
Section: Pulmonary Function and Loss Of Optimal Exercise Capacitymentioning
confidence: 99%
“…10 Bleomycin can cause dose-dependent alveolitis with nodular infiltrates and fibrosis in 3-4% of treated subjects; this risk is higher in patients who need oxygen therapy. 11,12 Melphalan and azathioprine have been described to elicit (rarely) interstitial alveolitis and chronic bronchitis, respectively, 13,14 and interleukin-2 can cause non-cardiogenic pulmonary edema. 15 Restrictive and obstructive respiratory impairment have been reported in children after bone marrow transplant; they appear to be associated with heavy pre-transplantation drug therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, this issue is debatable. 2,3 Nevertheless, it may be clinically relevant as many of the patients who receive bleomycin therapy for a variety of disorders are relatively young and may subsequently undergo surgery where general anaesthesia would be considered. Awareness and knowledge of these risk factors would certainly prove invaluable in preventing/ avoiding perioperative complications in a patient with prior exposure to bleomycin.…”
Section: Replymentioning
confidence: 99%
“…Even a modest increase in fraction of inspired oxygen (FiO 2 ) to 0.32 or 0.45, intra-operatively, has reportedly resulted in lung toxicity and death. 2 Further, the duration of this relationship is not well characterised. An exposure to Bleomycin in the past six months is considered by some to be a significant risk factor; 2 however for delivery of HBOT, even a remote history of Bleomycin therapy is an absolute contraindication.…”
mentioning
confidence: 99%